South African Renal Registry Annual Report 2020 - Davids, M Razeen; Jardine, Thabiet; Marais, Nicola; Sebastian, Sajith; Jacobs, Julian (African Journal of Nephrology, 2022)
The ninth annual report of the South African Renal Registry summarises the December 2020 data on kidney replacement therapy (KRT) for patients with kidney failure in South Africa. The numbers of patients reported here are substantially lower than those recorded in the previous report. This is likely the result of several factors, including larger numbers of deaths from COVID-19 and other causes, delayed initiation of KRT due to the pandemic, and challenges with data submission to the registry during a period when personnel were overwhelmed with clinical responsibilities related to the pandemic. In December 2020, the number of patients who were being treated with chronic dialysis or transplantation stood at 8 734, a prevalence of 146 per million population (pmp). The prevalence of South Africans accessing treatment in the private healthcare sector was 729 pmp, whereas it was 44 pmp in the chronically under-resourced public sector, well below the rate reported for 1994.